Water content monitoring in water-in-oil emulsions using a delay line cell (2023)
The extraction process of crude oil requires addition of water, resulting in complex emulsions, in which the phases must be separated before the petrochemical processing starts. An ultrasonic cell may be used to determine in real time the water content in water-in-crude oil emulsions. The water content of emulsions can be related to parameters, such as propagation velocity, density and relative attenuation. The ultrasonic measurement cell developed here is composed of two piezoelectric transducers, two rexolite buffer rods, and a sample chamber. It is an inexpensive and robust system. The cell measures the parameters at different temperatures and flow conditions. The tests were performed using emulsions with water volume concentrations from 0% to 40%. The experimental results show that this cell is able to obtain more precise parameters, when compared to similar ultrasonic techniques. The data acquired in real time may be used to improve the emulsion separation, decreasing greenhouse gases and energy requirements